Analisis Swot Islamic Marketing Pada Usaha Kain Tenun Songket Di Kota Palembang - Maya, Maya; Wilian, Armansyah; Umari, Zuul Fitriani (CV. ITTC INDONESIA, 2023)
This thesis research began with the songket business which marketed its products in terms of relatively low prices, but only a small number of devotees. As for the songket business which continuously promotes its consumers, there has been no increase. Then in other songket businesses, seen through the price offered is higher but still in demand by consumers. The purpose of this study was to analyze the SWOT of Islamic marketing (Islamic marketing) in the songket woven business in the city of Palembang. This type of research is field research with primary and secondary data sources. Collecting data through observation, interviews and documentation. The data analysis technique was carried out qualitatively descriptive using the SWOT method. The results of this study state that 1) the marketing strategy for songket businesses in Palembang city applies a marketing mix such as product, price, place, promotion, human resources, process, physical evidence, promises, patience, prioritizing consumer needs (customer centric). 2) Palembang's songket business applies four characteristics of Islamic marketing according to the study of Islamic figures Hermawan Kertajaya and Muhammad Syakir Sula namely rabbaniyah (spiritual or divine), ahlaqiyyah (ethical), al-waqi'iyyah (realistic), and insaniyyah (humanistic). 3) In the application of SWOT analysis, the songket woven fabric business in terms of strength has guaranteed quality products, more competitive prices than competitors, distribution avoids tyranny, promotions via the internet and social media. Weaknesses such as limited production capacity, promotions that have not been maximized, and limited marketing. Opportunities in the form of people's purchasing power tend to be consumptive, growth in the community's economic level, high demand for products. As well as threats in the form of inflation, the emergence of similar products made of machines, and business strategies that are easy to imitate.